2016
DOI: 10.1016/j.foodchem.2016.02.145
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of cod (Gadus morhua) protein hydrolysates: Fractionation and characterisation of peptide fractions

Abstract: This study aimed to characterise peptide fractions (>5kDa, 3-5kDa and <3kDa) with antioxidative activity obtained from a cod protein hydrolysate. The free amino acids in all fractions were dominated by Ala, Gly, Glu and Ser. The total amino acid composition had high proportions of Lys, Ala and Glu. The 3-5kDa and <3kDa fractions were further fractionated by size exclusion chromatography. All sub-fractions showed high Fe(2+) chelating activity. The DPPH radical-scavenging activity of the 3-5kDa fraction was exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(47 citation statements)
references
References 42 publications
(38 reference statements)
4
43
0
Order By: Relevance
“…Iron(III) 2‐ethylhexanoate, iron(III) acetylacetonate, copper(II) 2‐ethylhexanoate, and copper(II) acetylacetonate were chosen as metal sources for their solubility in oil. Two amino acids, L‐tryptophan and L‐lysine, were used at 11 mM, of which the metal chelation activity has been well studied . Table shows oxidation of metal‐containing SBO and the effect by L‐tryptophan and L‐lysine in the presence of a metal.…”
Section: Resultsmentioning
confidence: 99%
“…Iron(III) 2‐ethylhexanoate, iron(III) acetylacetonate, copper(II) 2‐ethylhexanoate, and copper(II) acetylacetonate were chosen as metal sources for their solubility in oil. Two amino acids, L‐tryptophan and L‐lysine, were used at 11 mM, of which the metal chelation activity has been well studied . Table shows oxidation of metal‐containing SBO and the effect by L‐tryptophan and L‐lysine in the presence of a metal.…”
Section: Resultsmentioning
confidence: 99%
“…GPH5 (<1 kDa) showed the highest antioxidant activities. Many studies have reported that low‐molecular‐weight peptides showed higher antioxidant activity (Shi et al ., ; Sabeena Farvin et al ., ). The trend of antioxidant activity was as follows: GPH5 (<1 kDa) > GPH4 (1–3 kDa) > GPH1 (>10 kDa) > GPH2 & GPH3 (3–10 kDa), which was connected to the amount of hydrophobic and aromatic amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…Protein hydrolysates from various sources have been reported to possess antioxidant activities, such as mackerel (Wu et al ., ), hoki (Mendis et al ., ), salmon (Ahn et al ., ), tilapia (Kangsanant et al ., ), cod (Sabeena Farvin et al ., ) and grass carp (Cai et al ., ). Grass carp ( Ctenopharyngodon idella ) is one of the ‘four major cultured fish species’ in China, and it has an annual production that exceeded 5.6 × 10 6 t in 2015, but it has not been developed into a high‐value product.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated earlier that protein hydrolysates from fi sh proteins are known for their antioxidant activity (6,(13)(14)(15)(16)(17). There are fewer reports about antioxidant activity of chicken protein-derived peptides (18,19), and only one study has compared fi sh with avian muscle hydrolysates (20); however, this study is without an in vitro digestion step.…”
Section: Antioxidant Activity In the Cells And Cellular Metabolic Energymentioning
confidence: 99%